A high thermal conductivity boron nitride-based interface material and preparation method thereof
By coating the silver layer with boron nitride powder and mixing it with graphene, nanosilver particles and nanoenhancers to form a multi-layer structure of highly thermally conductive boron nitride-based interface material, the weight and mechanical rigidity limitations of existing materials in lightweight and flexible applications are solved, and long-term stability and oxidation resistance are improved at high temperatures. At the same time, the service life and self-healing ability of the material have also been significantly improved.
Patent Information
- Application Number
- CN202411006871.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-25
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-07-25
AI Technical Summary
The existing high thermal conductivity interface materials have weight and mechanical rigidity limitations in lightweight and flexible applications, while the long-term stability and oxidation resistance at high temperatures are insufficient, and the application of a single boron nitride in composite materials is limited by its high hardness and high brittleness.
By coating the silver layer with boron nitride powder to improve binding force and thermal interface properties with the silicone matrix, and mixing it with graphene, nanosilver particles and nanoenhancing agents, a multi-layer structure of highly thermally conductive boron nitride-based interface material, including the first, second and third layers, each layer of material contains thermally conductive particles, self-healing microcapsules, magnetic nanoparticles Fe3O4 and metal aluminum foam.
The thermal conductivity, mechanical strength and flexibility of the material have been significantly improved, and its service life has also been greatly increased. It can repair itself under high load or high temperature conditions to maintain its structural and functional integrity.
Smart Images

Figure CN118876510B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of interface material preparation, and in particular to a high thermal conductivity boron nitride-based interface material and a preparation method thereof. Background Art
[0002] In modern industrial applications, especially in the fields of electronic equipment, aerospace, automotive manufacturing and high-performance computers, there is an increasing demand for high thermal conductivity materials. Equipment in these applications often face severe thermal management challenges, requiring materials that not only have excellent thermal conductivity but also can withstand mechanical stress and environmental influences. To this end, researchers and engineers have been seeking new materials that can effectively conduct and manage heat flow. Although traditional thermal interface materials (TIMs) such as copper and aluminum have good thermal conductivity, their weight and mechanical rigidity often limit their use in lightweight and flexible applications. In addition, the long-term stability and oxidation resistance of these metal materials at high temperatures are often insufficient, especially in applications that require high performance for a long time. Therefore, the development of a new type of high thermal conductivity interface material that can simultaneously have high thermal conductivity, excellent mechanical strength and good environmental stability has become an important direction of materials science research. Boron nitride is a ceramic material with good thermal conductivity. Due to its chemical stability and excellent electrical insulation, it has been widely studied for use in thermal management systems. However, the application of single boron nitride in composite materials is limited by its high hardness and brittleness, which leads to its unsatisfactory performance when dealing with mechanical stress.
[0003] To solve these problems, researchers have tried to combine boron nitride with other types of nanomaterials, but the existing combinations are only combined with other single functional materials or the interface is not layered to achieve the expected strength, hardness, recovery and other effects, and the shape of the interface is not designed and processed. For example, it is not combined with other nano-enhanced materials according to the material's special effects, resulting in the thermal conductivity, mechanical strength and flexibility of the interface material failing to meet the expected requirements. In addition, the service life and reliability of the material cannot meet the expected requirements. The lack of self-healing ability to help repair damaged parts and restore their heat conduction paths while meeting the thermal conductivity makes the material unable to maintain a long service life and stability under extreme conditions. Summary of the invention
[0004] In view of the above problems mentioned in the prior art, the present invention provides a high thermal conductivity boron nitride-based interface material and a preparation method thereof. The method firstly coats a layer of silver on boron nitride powder to improve the bonding force with a silica gel matrix and the thermal interface performance; secondly, the treated boron nitride powder is evenly mixed with graphene, nano silver particles and a nano reinforcing agent to form a mixture 1; the mixture 1 is again divided into three parts in a ratio of 35%:30%:35%, and functional materials are added to each mixture to form layer raw materials; then the layer raw materials are respectively mixed with the silica gel matrix in a high shear mixer; the raw materials mixed with the silica gel matrix are again poured into a honeycomb structure layered mold in sequence to form the first layer, the second layer and the third layer of the high thermal conductivity boron nitride-based interface material; finally, the pre-cured material is cured at 200°C for 4 hours to form a boron nitride-based interface material with a honeycomb structure. In the present application, the layer materials mixed with the silicone matrix are poured into the honeycomb structure layered mold in sequence to form the first layer, the second layer, and the third layer of the high thermal conductivity boron nitride-based interface material. The three-layer interface material structure formed by the self-healing microcapsules, magnetic nanoparticles Fe3O4, and metal aluminum foam containing thermal conductive particles between each layer of the material not only improves the thermal conductivity, mechanical strength and flexibility of the interface material, but also greatly improves the service life.
[0005] The present application provides a method for preparing a high thermal conductivity boron nitride-based interface material, which is characterized by comprising the steps of:
[0006] S1: The boron nitride powder is surface functionalized and coated with a layer of silver to improve the bonding strength and thermal interface performance with the silica matrix;
[0007] S2: mixing the treated boron nitride powder with graphene, nanosilver particles and nanoreinforcement agent to form a mixture 1, using a high shear mixer to ensure uniform dispersion of the components; the nanoreinforcement agent is selected from carbon nanotubes or borate fibers;
[0008] S3: Divide the mixture 1 into three parts in a ratio of 35%:30%:35%, namely the first mixture, the second mixture, and the third mixture, and add functional materials to each mixture to form the raw materials of the layer:
[0009] The first mixture is added with self-healing microcapsules with heat transfer oil to form a first layer of raw materials, wherein the shell of the self-healing microcapsules is made of silicone resin, a high temperature resistant material;
[0010] The second mixture is added with magnetic nanoparticles Fe3O4 to form the second layer of raw materials;
[0011] The third mixture is added with nano-aluminum metal foam to form the third layer of raw materials;
[0012] S4: mixing the first layer raw material, the second layer raw material, and the third layer raw material with the silica gel matrix in a high shear mixer to ensure that the components are evenly dispersed;
[0013] S5: pouring the first layer raw material, the second layer raw material, and the third layer raw material mixed with the silica gel matrix into the honeycomb structure layered mold in order to form the first layer, the second layer, and the third layer of the high thermal conductivity boron nitride-based interface material, and pre-curing at a temperature of 150° C. for 1 hour; wherein, before pouring into the honeycomb structure layered mold, adding a silane coupling agent γ-methacryloxypropyltrimethoxysilane to each layer of the material to enhance the bonding force between different layers;
[0014] S6: Curing the pre-cured material at 200° C. for 4 hours to form a boron nitride-based interface material with a honeycomb structure.
[0015] Preferably, S1: subjecting the boron nitride powder to surface functionalization treatment and coating a layer of silver to improve the bonding strength with the silica gel matrix and the thermal interface performance; wherein the surface functionalization treatment is performed by electroplating method, and the thickness of the silver layer coated is 0.5 to 10 microns.
[0016] Preferably, the average particle size of the nanosilver particles ranges from 10 to 100 nanometers; the first mixture is added with self-healing microcapsules containing heat-conducting oil to form a first layer of material, wherein the shell of the self-healing microcapsules is made of polyurethane, the filling rate of the heat-conducting oil is 50%-70% of the total volume of the microcapsules, and the average diameter of the microcapsules is 10 microns to 200 microns.
[0017] Preferably, S5: pouring the first layer material, the second layer material and the third layer material mixed with the silicone matrix into the honeycomb structure layered mold in sequence to form the first layer, the second layer and the third layer of the high thermal conductivity boron nitride-based interface material, wherein thermal conductive particles are contained between each layer of material to enhance the thermal and mechanical connection between the layers; the silicone matrix is a two-component RTV silicone, and the mixing process is carried out in a high shear mixer, the speed of the mixer is set at 1000 to 3000 rpm, and the mixing time is 5 to 15 minutes to ensure uniform mixing.
[0018] Preferably, the preparation of the second layer material includes surface modification and pre-dispersion of the nanoparticles Fe3O4 by high-energy ball milling before mixing the magnetic nanoparticles Fe3O4 with boron nitride powder, graphene and silica gel matrix, and then applying an external magnetic field during the manufacturing process to guide the nanoparticles Fe3O4 to arrange along a predetermined path before curing, so as to adjust their thermal conductivity and magnetic responsiveness in the finished product.
[0019] The present application also provides a high thermal conductivity boron nitride-based interface material, wherein the first layer of the high thermal conductivity boron nitride-based interface material is composed of the following components in weight percentage:
[0020] Boron nitride powder: 40%-50%, wherein the surface of the boron nitride powder is functionalized and coated with a layer of silver by chemical vapor deposition;
[0021] Graphene: 10%-20%;
[0022] Silica gel matrix: 10%-20%;
[0023] Nanosilver particles: 5%-15%;
[0024] Nano-enhancer carbon nanotubes: 2%-10%, forming a three-dimensional network structure together with nano-silver particles and graphene;
[0025] Self-healing microcapsules (including heat transfer oil): 5%-15%;
[0026] The second layer of the high thermal conductivity boron nitride-based interface material is composed of the following components in weight percentage:
[0027] Boron nitride powder: 40%-50%, wherein the surface of the boron nitride powder is functionalized and coated with a layer of silver by chemical vapor deposition;
[0028] Graphene: 10%-20%;
[0029] Silica gel matrix: 10%-20%;
[0030] Nanosilver particles: 5%-15%;
[0031] Nano-enhancer carbon nanotubes: 2%-10%, forming a three-dimensional network structure together with nano-silver particles and graphene;
[0032] Magnetic nanoparticles Fe3O4: 5%-10%;
[0033] The third layer of the high thermal conductivity boron nitride-based interface material is composed of the following components in weight percentage:
[0034] Boron nitride powder: 40%-50%, wherein the surface of the boron nitride powder is functionalized and coated with a layer of silver by chemical vapor deposition;
[0035] Graphene: 10%-20%;
[0036] Silica gel matrix: 10%-20%;
[0037] Nanosilver particles: 5%-15%;
[0038] Nano-enhancer carbon nanotubes: 2%-10%, forming a three-dimensional network structure together with nano-silver particles and graphene;
[0039] Add nano aluminum metal foam: 5%-10%;
[0040] Among them, the second layer is between the first and third layers. The high thermal conductivity boron nitride-based interface material has a honeycomb structure to optimize thermal conductivity and mechanical properties. The honeycomb structure is composed of a periodic porous network, and the diameter of each hole is between 10 microns and 100 microns.
[0041] Preferably, the thickness of the silver layer coated with a layer of silver is 0.5 to 10 microns.
[0042] Preferably, the average particle size of the nanosilver particles ranges from 10 to 100 nanometers; the shell of the self-healing microcapsule is made of polyurethane, the filling rate of the thermal oil is 50%-70% of the total volume of the microcapsule, and the average diameter of the microcapsule is 10 microns to 200 microns.
[0043] Preferably, the second layer is between the first layer and the third layer, wherein heat conductive particles are contained between each layer of material to enhance the thermal and mechanical connection between the layers.
[0044] Preferably, the silicone matrix is a two-component RTV silicone.
[0045] The present invention provides a high thermal conductivity boron nitride-based interface material and a preparation method thereof, which can achieve the following beneficial technical effects:
[0046] 1. The present invention first coats a layer of silver on boron nitride powder to improve the bonding force and thermal interface performance with a silica gel matrix; secondly, the treated boron nitride powder is uniformly mixed with graphene, nano silver particles and a nano reinforcing agent to form a mixture 1; the mixture 1 is again divided into three parts according to a ratio of 35%:30%:35%, and functional materials are added to each mixture to form layer raw materials; then the layer raw materials are respectively mixed with a silica gel matrix in a high shear mixer; the raw materials mixed with the silica gel matrix are again poured into a honeycomb structure layered mold in sequence to form a first layer, a second layer and a third layer of a high thermal conductivity boron nitride-based interface material; finally, the pre-cured material is cured at 200° C. for 4 hours to form a honeycomb structure boron nitride-based interface material. In the present application, the layer materials mixed with the silicone matrix are poured into the honeycomb structure layered mold in sequence to form the first layer, the second layer, and the third layer of the high thermal conductivity boron nitride-based interface material. The three-layer interface material structure formed by the self-healing microcapsules, magnetic nanoparticles Fe3O4, and metal aluminum foam containing thermal conductive particles between each layer of the material not only improves the thermal conductivity, mechanical strength and flexibility of the interface material, but also greatly improves the service life.
[0047] 2. The present invention uses a combination of boron nitride, graphene, nanosilver particles and nano-enhancers (carbon nanotubes or borate fibers) in this technical solution. This combination of multiple components innovatively solves the limitations of a single material in thermal conductivity or mechanical properties. This multi-component nanocomposite material provides excellent thermal conductivity and enhanced mechanical stability. Graphene and nanosilver particles greatly increase the thermal conductivity of the composite material, while carbon nanotubes and borate fibers enhance the mechanical strength and flexibility of the material, making the material suitable for high-performance industrial applications, such as effectively dissipating heat in electronic equipment and keeping the equipment working stably for a long time.
[0048] 3. The present invention adds self-healing microcapsules containing heat transfer oil to the first layer of material. These microcapsules can automatically release heat transfer oil to fill the cracks and restore the heat conduction path when the material has tiny cracks or damage. The self-healing technology significantly improves the reliability and durability of the material. Even if tiny damage occurs under high load or high temperature conditions, the material can self-repair and maintain its structural and functional integrity, thereby extending its service life and reducing maintenance costs. Magnetic nanoparticles Fe3O4 are added to the second layer of material to allow the material properties to be adjusted through an external magnetic field, changing the heat conduction path or increasing thermal isolation. The magnetic control layer provides a method for dynamically adjusting the material properties, increasing the applicability and functionality of the material. In applications that require rapid changes in thermal management strategies, such as in changing external environments, the performance and response speed of the device can be optimized by simply adjusting the magnetic field. An interface layer containing thermally conductive particles is added between each layer to enhance the thermal and mechanical connection between the layers and improve the structural integrity and thermal efficiency of the overall material. The addition of thermally conductive particles not only enhances the thermal conductivity between the layers, but also enhances the mechanical bonding between the layers, making the overall structure more stable. This design improves the performance of the material in complex application environments, especially those that require high mechanical strength and excellent thermal management. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0050] Figure 1 It is a schematic diagram of the steps of a method for preparing a high thermal conductivity boron nitride-based interface material of the present invention. DETAILED DESCRIPTION
[0051] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] Embodiment 1:
[0053] In view of the above problems mentioned in the prior art, in order to solve the above technical problems, as shown in the attached Figure 1 As shown: The present application provides a method for preparing a high thermal conductivity boron nitride-based interface material, characterized in that it includes the steps of:
[0054] S1: The boron nitride powder is subjected to surface functionalization treatment and coated with a layer of silver to improve the bonding force with the silica gel matrix and the thermal interface performance; the surface functionalization treatment of the boron nitride powder is aimed at coating a layer of silver to improve the bonding force between the powder and the silica gel matrix and the overall thermal interface performance. This step is the basis for preparing high thermal conductivity interface materials. The key is to achieve good bonding between the boron nitride powder and the silver layer and ensure that the silver layer can effectively improve the thermal conductivity. The purpose of surface functionalization treatment is to increase the surface activity of the boron nitride powder, thereby improving its adhesion to the silver layer, and to use chemical or physical methods to change the properties of the surface of the boron nitride powder, such as through chemical vapor deposition (CVD), plasma treatment or surface chemical modification, etc., to introduce functional groups that can bind well with silver. Technology selection uses electroplating, chemical plating or physical vapor deposition (PVD) and other technologies to uniformly coat a layer of silver on the surface of the boron nitride powder; coating thickness: usually in the range of 0.5 to 10 microns, adjusted according to the thermal interface performance requirements of the final application. The following examples describe how to coat a layer of silver on boron nitride powder by chemical plating. The silver layer coating of boron nitride powder is prepared by: boron nitride powder, silver plating solution (containing silver nitrate and a reducing agent such as formaldehyde). The boron nitride powder is cleaned to remove surface impurities. It can be washed with deionized water or an appropriate organic solvent (such as ethanol). The plasma surface treatment technology is used to generate active groups on the surface of the boron nitride powder to enhance its adhesion to silver. The pretreated boron nitride powder is immersed in an activation solution containing a catalyst (such as a palladium salt) to form a thin catalyst layer to promote uniform plating of silver. The activated boron nitride powder is transferred to the silver plating solution. Under controlled conditions (such as room temperature, pH value is about 9-11), a silver layer is deposited on the powder surface by chemical plating. The plating process usually lasts from several minutes to tens of minutes, and the specific time is adjusted according to the required silver layer thickness. After the plating is completed, the silver-coated boron nitride powder is removed from the plating solution, rinsed with deionized water, and then dried under mild conditions (such as 40-60°C). The surface of the treated boron nitride powder is evenly coated with a layer of silver with a thickness of about 5 microns. The material prepared by this method shows excellent thermal conductivity and improved bonding between the powder and the silica gel matrix.
[0055] S2: The treated boron nitride powder is mixed with graphene, nanosilver particles and nano-enhancers to form a mixture 1, and a high shear mixer is used to ensure that the components are evenly dispersed; the nano-enhancer is selected from carbon nanotubes or borate fibers; the key process of preparing a high thermal conductivity boron nitride-based interface material involves mixing the surface-treated boron nitride powder with other nano-scale fillers to enhance the thermal conductivity and mechanical properties of the composite material. The key to the success of this step is to ensure that the various nanoparticles are evenly dispersed in the matrix to avoid aggregation, thereby maximizing heat transfer and enhancing the overall performance of the material. The boron nitride powder has been surface functionalized, such as coated with a silver layer, to enhance compatibility and interfacial bonding with other components. Graphene is added as a key component of the heat conduction path due to its extremely high thermal conductivity and mechanical strength. Nano-silver particles provide additional heat conduction channels and enhance the electrical properties of the composite material through their good electrical conductivity. Materials such as carbon nanotubes or borate fibers can enhance the mechanical strength and structural stability of the composite material while providing flexibility and durability. The following example describes how to mix treated boron nitride powder, graphene, nanosilver particles and nanoenhancers to form a uniform mixture 1. The preparation of the mixed material includes preparing boron nitride powder (coated with a silver layer), graphene sheets, nanosilver particles, carbon nanotubes or borate fibers. The graphene, nanosilver particles and selected nanoenhancers (carbon nanotubes or borate fibers) are cleaned and pretreated on the surface to ensure that there are no impurities and to optimize their surface properties to enhance the binding with the boron nitride powder; the pretreated boron nitride powder, graphene, nanosilver particles and nanoenhancer are added to a high shear mixer; the mixer speed is set at 1000 to 3000 rpm and the mixing time is 10 to 30 minutes to ensure that all components are evenly dispersed without obvious aggregation or separation. The mixed mixture 1 was tested for uniformity and, if necessary, secondary mixing was performed to eliminate any unevenly dispersed areas; the particle distribution state was checked by SEM (scanning electron microscopy) to confirm that no large aggregates were present; the obtained mixture 1 showed good uniformity and excellent dispersion of each component, laying a solid foundation for further composite material processing.
[0056] S3: Divide the mixture 1 into three parts in a ratio of 35%:30%:35%, namely the first mixture, the second mixture, and the third mixture, and add functional materials to each mixture to form the raw materials of the layer:
[0057] The first mixture is added with self-healing microcapsules containing heat-conducting oil to form a first layer of raw materials; wherein the shell of the self-healing microcapsules is made of silicone resin, a high-temperature resistant material;
[0058] The second mixture is added with magnetic nanoparticles Fe3O4 to form the second layer of raw materials;
[0059] The third mixture is added with nano-aluminum metal foam to form the third layer of raw materials;
[0060] In some embodiments, the material added to the first mixture includes self-healing microcapsules of thermal oil, which provide self-healing ability, so that the material can automatically repair when tiny cracks or damage occur, maintain or restore the heat conduction path. The material added to the second mixture: magnetic nanoparticles Fe3O4, which allow the thermal properties of the material to be regulated by an external magnetic field to achieve dynamic thermal management. The material added to the third mixture: nano-aluminum metal foam, which increases the lightweight characteristics of the material and improves the thermal conductivity efficiency while enhancing the structural strength. . Mixture 1 includes boron nitride powder, graphene, nano-silver particles, and nano-enhancers; functional materials include self-healing microcapsules of thermal oil, magnetic nanoparticles Fe3O4, and nano-aluminum metal foam. Mixture 1 is accurately weighed according to the ratio of 35%, 30%, and 35%, respectively, and used for the preparation of three different layer raw materials. The self-healing microcapsules of thermal oil are added to the first mixture, and mixed thoroughly to ensure that the microcapsules are evenly distributed. The magnetic nanoparticles Fe3O4 are added to the second mixture, and the uniform mixing is also ensured to achieve consistency in magnetic response. Add nano aluminum metal foam to the third mixture and mix thoroughly to evenly distribute the aluminum foam to optimize structural strength and thermal conductivity. Perform a uniformity test on each mixed material to ensure that the added functional materials are not aggregated to ensure the performance consistency of each layer of material. Optionally, use appropriate detection techniques (such as microscopy) to verify the distribution of functional materials and the uniformity of the overall mixture. Through precise proportioning and mixing, three layers of raw materials with different functions are prepared. Each material has its specific properties, which provides a basis for the performance optimization of the final multilayer interface material.
[0061] S4: The first layer of raw materials, the second layer of raw materials, and the third layer of raw materials are mixed with the silica matrix in a high shear mixer to ensure that each component is evenly dispersed; focus on mixing the raw materials prepared in the previous steps with the silica matrix to ensure uniform distribution between the functional filler and the silica matrix to improve the mechanical strength, thermal stability and overall performance of the final product. As an important component, the silica matrix not only provides structural support, but also helps to enhance the overall temperature resistance and electrical insulation properties of the composite material. The first layer of raw materials uses self-healing microcapsules containing thermal oil; the second layer of raw materials uses Fe3O4 containing magnetic nanoparticles; the third layer of raw materials uses nano-aluminum metal foam; the silica matrix uses two-component room temperature curing silica gel, and the high shear mixer is used for efficient mixing equipment that can evenly disperse particles under high shear force. In some embodiments, the three layers of raw materials are mixed with the silica matrix to prepare the silica matrix. The two components of the two-component silica gel are prepared according to the manufacturer's recommended ratio, usually a 1:1 ratio. Mixing the first layer of raw materials Add the prepared first layer of raw materials (containing self-healing microcapsules) to a high shear mixer, add an equal proportion of the silica matrix, set the mixer speed to 2000 rpm, and mix for 10 minutes to ensure that the microcapsules are evenly distributed in the silica matrix. Mixing the second layer of raw materials, repeat the mixing steps of the first layer, but add the second layer of raw materials containing magnetic nanoparticles Fe3O4, and also ensure that the magnetic nanoparticles are evenly distributed in the silica matrix so that the expected thermal regulation effect can be achieved under the action of the external magnetic field. Mixing the third layer of raw materials Using the same mixing steps, mix the third layer of raw materials containing nano-aluminum metal foam with the silica matrix to ensure that the aluminum foam is evenly distributed in the silica matrix to improve the lightweight and thermal conductivity of the structure. After each mixing, the mixture is visually and mechanically inspected to ensure that there are no unmixed aggregates. If necessary, fine-tune the mixing parameters or repeat the mixing process to achieve optimal uniformity.
[0062] S5: pour the first layer of raw materials, the second layer of raw materials, and the third layer of raw materials mixed with the silica gel matrix into the honeycomb structure layered mold in order to form the first layer, the second layer, and the third layer of the high thermal conductivity boron nitride-based interface material, and pre-cure at a temperature of 150°C for 1 hour; wherein, before pouring into the honeycomb structure layered mold, add a silane coupling agent γ-methacryloxypropyl trimethoxysilane to each layer of the material to enhance the bonding force between different layers; step S5 mainly involves correctly stacking the three layers of mixed raw materials and pre-curing them under controlled conditions to form a structurally complete multi-layer high thermal conductivity boron nitride-based interface material. The use of the honeycomb structure layered mold plays a key role in this process because it not only provides the necessary shape and size for the material, but also helps to improve the heat transfer and mechanical stability of the final product due to its unique design. In some embodiments, the mold is designed as a honeycomb structure, and the diameter of each honeycomb unit can be adjusted as needed, with a common range of 10 microns to 100 microns. The mold material needs to be able to withstand high temperatures and chemical corrosion, and is usually made of stainless steel or special alloys. The mold is designed with multiple layers of partitions inside, and different material layers can be poured in sequence. The partitions are withdrawn before the material solidifies to ensure good connection between the layers. Clean and preheat the mold to 150℃ to eliminate any possible moisture or impurities to ensure that there are no defects caused by impurities when the material solidifies. First, the first layer of raw materials containing self-healing microcapsules is slowly poured into the bottom layer of the mold to ensure that the materials are evenly distributed; then, the second layer of raw materials containing magnetic nanoparticles Fe3O4 is poured and laid evenly; finally, the third layer of raw materials containing nano-aluminum metal foam is poured into the top layer to complete the filling of all layers. Pre-curing treatment Place the filled mold in an oven at a temperature of 150℃ for 1 hour. This step is designed to partially cure the silicone matrix, enough to maintain the shape and integrity of the layer material, but not completely cured, so that the chemical and mechanical bonding between the layers can be better achieved in the subsequent full curing step. Cooling and demoulding, after pre-curing, let the mold cool naturally to room temperature, then carefully remove the semi-cured material from the mold and check the bonding between the layers and any visible defects.
[0063] S6: The pre-cured material is cured at 200°C for 4 hours to form a honeycomb structured boron nitride-based interface material. Step S6 is to complete the final curing process of the high thermal conductivity boron nitride-based interface material. In this step, the pre-cured multilayer material is further heat treated to fully cure, ensure the maximum bonding force between the layers of material, and give the material the final mechanical and thermal properties. The curing process is carried out at a higher temperature to promote the cross-linking reaction in the silicone matrix, thereby forming a strong and stable honeycomb structure. The temperature of the curing process is 200°C, which is the ideal temperature to ensure that the silicone matrix is fully cured and can achieve the best physical and chemical properties. The curing process takes 4 hours, which is long enough to ensure that the cross-linking reaction in the silicone matrix is fully carried out so that the material achieves the expected mechanical strength and thermal stability. The curing process is usually carried out in an oven to control the environmental conditions to avoid any potential environmental pollution or humidity. After the pre-curing treatment completed in step S5, the obtained three-layer structure material is taken out and prepared for further curing. The oven is preheated to 200°C to ensure that the set temperature is reached before the material enters the oven to avoid temperature fluctuations affecting the curing effect. The pre-cured material is placed in an oven and set to 4 hours, maintaining a constant temperature of 200°C. The material is heated evenly in the oven to ensure that each layer can be fully cured. After the curing is completed, the material is allowed to cool naturally to room temperature in the oven to avoid thermal stress caused by rapid cooling. The cured material is taken out and visually and physically inspected to ensure that there are no cracks or delamination. Necessary tests such as thermal conductivity tests, compressive strength tests, and thermal cycle tests are carried out to evaluate the comprehensive performance of the material and check the integrity and uniformity of the honeycomb structure to ensure that it meets the design specifications.
[0064] In some embodiments, S1: the boron nitride powder is subjected to surface functionalization treatment, and a layer of silver is coated to improve the bonding force and thermal interface performance with the silica gel matrix; wherein the surface functionalization treatment adopts an electroplating method, and the thickness of the silver layer coated with a layer of silver is 0.5 to 10 microns. This step involves surface functionalization treatment of the boron nitride powder, specifically coating a layer of silver by electroplating, which is intended to improve the bonding force between the boron nitride powder and the silica gel matrix and enhance the thermal interface performance of the overall material. The addition of the silver layer not only enhances the thermal conductivity of the powder, but also optimizes the performance of the material in electronic applications due to its good electrical conductivity. The key considerations for silver layer electroplating include a silver layer thickness of 0.5 to 10 microns, which allows the silver layer to be thick enough to ensure good thermal conductivity and electrical conductivity without being too heavy to affect other physical properties of the material. The electroplating solution contains a suitable concentration of silver ions, and silver nitrate solution is usually used as the silver source; the current density and electroplating time need to be carefully controlled to ensure the uniformity and adhesion strength of the silver layer. In a real-time example, the boron nitride powder is first cleaned during pretreatment to remove any impurities or oil on the surface. Gently wash with deionized water and non-ionic surfactant, and then dry at 60°C. Prepare a plating solution containing silver nitrate, and adjust the concentration to a level suitable for the growth of the silver layer. In order to improve the efficiency of electroplating and the quality of the silver layer, add an appropriate amount of brightener and stabilizer. During electroplating, immerse the dry boron nitride powder in the electroplating tank, use a special stirring device to keep the powder suspended to avoid aggregation, set the current density of the power supply to 1 to 3A / dm2, adjust the electroplating time according to the required silver layer thickness, generally between 10 and 30 minutes, and monitor the pH value and temperature of the solution during the electroplating process to ensure that it is maintained under the best electroplating conditions. After the electroplating is completed, the boron nitride powder is removed from the electroplating solution, rinsed thoroughly with deionized water to remove the residual electroplating solution on the surface, and dried under mild conditions to solidify the silver layer and prevent oxidation. During quality inspection, a scanning electron microscope (SEM) is used to check the uniformity and continuity of the silver layer, and adhesion strength tests and thermal conductivity tests are performed to evaluate the performance of the silver layer.
[0065] In some embodiments, the average particle size of the nanosilver particles ranges from 10 to 100 nanometers; the first mixture is added with self-healing microcapsules containing heat transfer oil to form a first layer of material, wherein the shell of the self-healing microcapsules is made of polyurethane, the filling rate of heat transfer oil is 50%-70% of the total volume of the microcapsules, and the average diameter of the microcapsules is 10 microns to 200 microns. The self-healing microcapsules in the first mixture of the present technical solution are one of the key innovations, aiming to increase the durability and reliability of the material. These microcapsules can release heat transfer oil when the material is damaged, automatically repair cracks or fractures, thereby restoring the thermal conductivity and structural integrity of the material. The average particle size of the nanosilver particles is 10 to 100 nanometers, and this size range ensures good dispersion and high surface area, enhancing thermal conductivity. The shell material of the self-healing microcapsules is polyurethane, which is selected for its good chemical stability and mechanical strength, and the filling rate of heat transfer oil accounts for 50%-70% of the total volume of the microcapsules, ensuring that enough repair material is released when needed. The microcapsules have a diameter of 10 to 200 microns, a size range that allows the microcapsules to be evenly distributed in the material while maintaining sufficient internal volume to store the repair oil. In some embodiments, a first layer of material containing self-healing microcapsules is prepared, and the preparation process of the microcapsules includes mixing a polyurethane precursor and a heat-conducting oil in a reaction vessel, controlling the ratio by interfacial polymerization technology to achieve the desired filling rate, wherein the polyurethane precursor solidifies at the oil-water interface to form a microcapsule shell. A stirring device is used to maintain a uniform stirring speed to ensure that the microcapsules are uniform in size. After the microcapsules are formed, unreacted substances are removed by filtering and washing steps, and then dried for subsequent use. Mixing the first batch of raw materials The prepared self-healing microcapsules are mixed with the pre-prepared boron nitride powder containing nanosilver particles, and the mixture is added to a high shear mixer to ensure that the microcapsules and nanosilver particles are evenly distributed in the boron nitride powder, and the mixing parameters are adjusted to avoid damaging the integrity of the microcapsules. The first layer of mixed raw materials is tested for uniformity, the distribution of microcapsules and nanosilver particles is confirmed using a microscope, and preliminary thermal and mechanical properties tests are performed to evaluate the initial performance of the material. This first layer of material containing self-healing microcapsules can be used to manufacture heat dissipation components for high-performance electronic devices that require high durability and self-healing capabilities. This material can automatically repair itself when minor damage occurs, maintaining its thermal management performance and extending the service life of the device.
[0066] In some embodiments, the S5: pour the first layer material, the second layer material, and the third layer material mixed with the silica gel matrix into the honeycomb structure layered mold in order to form the first layer, the second layer, and the third layer of the high thermal conductivity boron nitride-based interface material, wherein each layer of material contains thermal conductive particles to enhance the thermal and mechanical connection between the layers; the silica gel matrix is a two-component RTV silica gel, and the mixing process is carried out in a high shear mixer, the speed of the mixer is set at 1000 to 3000 rpm, and the mixing time is 5 to 15 minutes to ensure uniform mixing. The key in this step is to enhance the thermal and mechanical connection between the layers by adding thermal conductive particles between each layer of material, while ensuring the uniform distribution of each layer of material in the silica gel matrix, using two-component RTV silica gel as the matrix. This material maintains good physical properties at high temperatures due to its excellent thermal stability and mechanical strength, and is particularly suitable for the application of high thermal conductivity materials. The thermal conductive particles are usually metal or ceramic particles with high thermal conductivity, such as copper, silver or aluminum oxide. These particles are designed to enhance the efficiency of heat conduction between materials and to enhance the mechanical bonding between layers by physically embedding them. The characteristics of two-component RTV silicone. Two-component RTV silicone consists of two parts, one is a silicone rubber matrix and the other is a curing agent. After mixing the two components, the silicone can be cured at room temperature or slightly higher temperature to form a structure with good elasticity and heat resistance. Prepare a multilayer structure using two-component RTV silicone and thermally conductive particles. Prepare the thermally conductive particles. Select the appropriate size and material (for example, the average particle size of copper particles is 30 microns). Prepare the two components of the two-component RTV silicone. During the mixing process, add the first layer material (containing self-healing microcapsules), the second layer material (containing magnetic nanoparticles Fe3O4) and the third layer material (containing nano-aluminum metal foam) in a high shear mixer. Add an appropriate amount of thermally conductive particles to each layer of material. Add the pre-measured RTV silicone matrix and curing agent to each layer of material. Set the mixer speed between 1000 and 3000 rpm and mix for 10 minutes to ensure uniform mixing of the materials and the silicone. When filling the mold and building the layers, pour the mixed first layer of material into the pre-prepared and heated honeycomb structure mold to form the bottom layer, then pour the second layer of material, and then the third layer of material. After each pour, gently shake the mold to eliminate bubbles and ensure that there are no gaps between layers. Between pouring each layer of material, ensure that the previous layer is slightly cured to prevent interlayer mixing. Pre-curing and curing Pre-cure the material in the mold at 150°C for 1 hour, then transfer the mold to a 200°C oven for curing for 4 hours. During post-processing and inspection, remove the mold after cooling, check the integrity of the multi-layer structure and the bonding quality between each layer, and perform thermal conductivity and mechanical strength tests to verify the performance of the material.
[0067] In some embodiments, the preparation of the second layer of material includes surface modification and pre-dispersion of the Fe3O4 nanoparticles by high-energy ball milling before mixing the Fe3O4 nanoparticles with boron nitride powder, graphene and silica gel matrix, and then applying an external magnetic field to guide the Fe3O4 nanoparticles to be arranged along a predetermined path during the manufacturing process before curing to adjust their thermal conductivity and magnetic responsiveness in the finished product. The key to this step is to optimize the function of the Fe3O4 magnetic nanoparticles through advanced surface treatment and manufacturing technology, so that they have optimized thermal conductivity and the ability to respond to external magnetic fields in boron nitride-based interface materials. The introduction of this technology not only improves the physical properties of the material, but also brings new functionality to the application of the material, such as regulating the heat conduction path through a magnetic field. The purpose of high-energy ball milling of Fe3O4 nanoparticles is to modify the surface of Fe3O4 nanoparticles by physical methods, increase their surface roughness and activity, so that they can better combine with other components such as boron nitride and graphene in the subsequent process, and improve their dispersibility in the silica gel matrix. Before adding to the final mixture, ensure that the nanoparticles are evenly dispersed. The key to this step is to prevent aggregation, which will weaken the overall performance of the material. Before the material solidifies, an external magnetic field is applied to guide the magnetic nanoparticles Fe3O4 to arrange along a predetermined path. This step allows the thermal conductivity and magnetic response of the material to be optimized according to the design requirements. Prepare the second layer of material with magnetic field guidance function. High-energy ball milling of Fe3O4 nanoparticles. Place the Fe3O4 nanoparticles in a high-energy ball mill and use an appropriate amount of grinding media (such as carbide balls) for ball milling. The ball milling process is controlled within 2-4 hours to ensure that the particle surface is effectively modified. Pre-dispersion of nanoparticles. The ball-milled Fe3O4 nanoparticles are mixed with an appropriate amount of dispersant (such as a surfactant) and pre-dispersed using an ultrasonic treatment device for about 30 minutes to further improve their uniformity in the silica gel matrix. The pretreated Fe3O4 nanoparticles are mixed with boron nitride powder and graphene, and then gradually added to the two-component RTV silica gel. Use a high shear mixer to mix to ensure that all components are evenly distributed. The mixing time is controlled within 10-15 minutes. When applying an external magnetic field, first set up an external magnetic field device before the mixture is poured into the mold, adjust the strength and direction of the magnetic field according to the design requirements, and continue to apply the magnetic field during the curing process to ensure that the Fe3O4 nanoparticles are arranged along the predetermined path. Pour the treated mixture into a pre-prepared mold, and perform pre-curing and curing treatments under the condition of applying a magnetic field. After curing, test the thermal conductivity and magnetic response performance of the material to verify the success of the preparation process. Through this unique preparation process, the second layer of material not only has excellent thermal conductivity, but also can adjust its heat conduction path through an external magnetic field. This makes the material show great potential in high-tech applications that require dynamic adjustment of thermal management strategies, such as the heat dissipation system of electronic equipment.By precisely controlling the distribution and arrangement of nanoparticles, this material can also be used in sensors and other smart devices to take advantage of its magnetic response properties.
[0068] In one embodiment, in order to further improve the functionality of magnetic nanoparticles Fe3O4 and enhance its application effect in high thermal conductivity boron nitride-based interface materials, graphene is combined with another material to modify the surface of Fe3O4. The following is an innovative dual-material coating scheme that combines graphene and polyaniline. Graphene: Provides extremely high thermal conductivity and electrical conductivity, enhances the thermal and electrical conductivity of Fe3O4; Polyaniline (PANI): Has good environmental stability and adjustable electrical conductivity, and can provide additional regulation between magnetism and conductivity. Modification step: Surface activation First, the Fe3O4 particles are surface activated to increase their bonding with the coating material. Graphene layer deposition, grow a thin layer of graphene on the Fe3O4 surface by chemical vapor deposition (CVD) method. This step is intended to form a thermally and electrically conductive base layer. Polyaniline coating, using an in-situ polymerization method, covers a layer of polyaniline on the graphene coating. The polymerization reaction can be carried out directly on the Fe3O4 surface to form a uniform PANI layer. This layer not only enhances the environmental adaptability of Fe3O4, but also provides additional electrochemical stability. Heat treatment. The coated Fe3O4 particles undergo appropriate heat treatment to ensure the adhesion of the coating and the overall chemical stability. Enhanced versatility. The double-layer coating combining graphene and polyaniline not only improves thermal conductivity, but also increases the electrochemical activity of the material, making the Fe3O4 particles more effective in thermal management systems that require dynamic regulation. Optimized electromagnetic response. The introduction of polyaniline increases the electromagnetic response capability of Fe3O4, making its performance even better when affected by external electromagnetic fields, making it suitable for application in smart heat dissipation and electromagnetic shielding materials. Improved environmental stability. Polyaniline provides an excellent environmental protection layer and increases the service life of the particles in humid or corrosive environments. This unique dual-material combination strategy not only improves the performance of Fe3O4, but also opens up new avenues for more efficient and reliable thermal interface materials.
[0069] The present application also provides a high thermal conductivity boron nitride-based interface material, wherein the first layer of the high thermal conductivity boron nitride-based interface material is composed of the following components in weight percentage:
[0070] Boron nitride powder: 40%-50%, wherein the surface of the boron nitride powder is functionalized and coated with a layer of silver by chemical vapor deposition;
[0071] Graphene: 10%-20%;
[0072] Silica gel matrix: 10%-20%;
[0073] Nanosilver particles: 5%-15%;
[0074] Nano-enhancer carbon nanotubes: 2%-10%, forming a three-dimensional network structure together with nano-silver particles and graphene;
[0075] Self-healing microcapsules (including heat transfer oil): 5%-15%;
[0076] The second layer of the high thermal conductivity boron nitride-based interface material is composed of the following components in weight percentage:
[0077] Boron nitride powder: 40%-50%, wherein the surface of the boron nitride powder is functionalized and coated with a layer of silver by chemical vapor deposition;
[0078] Graphene: 10%-20%;
[0079] Silica gel matrix: 10%-20%;
[0080] Nanosilver particles: 5%-15%;
[0081] Nano-enhancer carbon nanotubes: 2%-10%, forming a three-dimensional network structure together with nano-silver particles and graphene;
[0082] Magnetic nanoparticles Fe3O4: 5%-10%;
[0083] The third layer of the high thermal conductivity boron nitride-based interface material is composed of the following components in weight percentage:
[0084] Boron nitride powder: 40%-50%, wherein the surface of the boron nitride powder is functionalized and coated with a layer of silver by chemical vapor deposition;
[0085] Graphene: 10%-20%;
[0086] Silica gel matrix: 10%-20%;
[0087] Nanosilver particles: 5%-15%;
[0088] Nano-enhancer carbon nanotubes: 2%-10%, forming a three-dimensional network structure together with nano-silver particles and graphene;
[0089] Add nano aluminum metal foam: 5%-10%;
[0090] Among them, the second layer is between the first and third layers. The high thermal conductivity boron nitride-based interface material has a honeycomb structure to optimize thermal conductivity and mechanical properties. The honeycomb structure is composed of a periodic porous network, and the diameter of each hole is between 10 microns and 100 microns.
[0091] In one embodiment, the optimal configuration is shown in the following table:
[0092]
[0093] By optimizing the ratio of boron nitride powder, graphene and nanosilver particles in each layer, as well as the use of nano-reinforcements, a balance between high thermal conductivity and good mechanical properties is achieved. By adding magnetic nanoparticles in the second layer and nano-aluminum metal foam in the third layer, the functional diversity of the material is increased, such as regulating thermal properties through magnetic fields, and improving structural strength and thermal efficiency through lightweight materials. The self-healing microcapsules in the first layer provide additional durability, allowing the material to repair itself after damage and maintain thermal conduction efficiency.
[0094] The following table is a comparison:
[0095]
[0096]
[0097] By comparing the ratio and the optimal ratio, it is found that: 1. In terms of thermal conductivity, the optimal ratio: the selected material ratio, such as high content of boron nitride powder and graphene, ensures high thermal conductivity. For example, the thermal conductivity measurement result of the optimal ratio is 300W / mK. Comparative ratio: lower boron nitride powder and graphene content may result in lower thermal conductivity. For example, the thermal conductivity of comparative ratios 1 and 2 is only 250W / mK and 270W / mK. 2. Mechanical strength: Optimal ratio: By including an appropriate amount of nano-enhancer carbon nanotubes and a moderate silicone matrix, thermal conductivity and mechanical strength are balanced. Assume that the tensile strength test result is 80MPa. Comparative ratio: A higher or lower silicone matrix ratio may result in structural weakening or excessive hardening, reducing applicability. The comparative ratio may only be 70MPa and 65MPa. 3. Cost efficiency: Optimal ratio: By balancing the use of expensive graphene and silver particles, the optimal ratio provides cost-effectiveness. The cost per square meter is 50USD. Comparison ratio: Higher usage of expensive materials increases costs to 60USD or 65USD. 4. In terms of manufacturing ease, the best ratio: Simplified processing reduces production errors and time, with an average production time of 5 hours / batch. Comparison ratio: More complex or precisely controlled ratios increase production time, which may take 6 or 7 hours / batch. Through the data, we can see that the best ratio provides better performance and value in terms of thermal conductivity, mechanical strength, cost efficiency and manufacturing ease.
[0098] In some embodiments, the silver layer coated has a thickness of 0.5 to 10 micrometers.
[0099] In some embodiments, the average particle size of the nanosilver particles ranges from 10 to 100 nanometers; the shell of the self-healing microcapsule is made of polyurethane, the thermal oil filling rate is 50%-70% of the total volume of the microcapsule, and the average diameter of the microcapsule is 10 microns to 200 microns.
[0100] In some embodiments, the second layer is between the first layer and the third layer, wherein thermally conductive particles are included between each layer of material to enhance thermal and mechanical connections between the layers.
[0101] In some embodiments, the silicone matrix is a two-component RTV silicone.
[0102] The present invention provides a high thermal conductivity boron nitride-based interface material and a preparation method thereof, which can achieve the following beneficial technical effects:
[0103] 1. The present invention first coats a layer of silver on boron nitride powder to improve the bonding force and thermal interface performance with a silica gel matrix; secondly, the treated boron nitride powder is uniformly mixed with graphene, nano silver particles and a nano reinforcing agent to form a mixture 1; the mixture 1 is again divided into three parts according to a ratio of 35%:30%:35%, and functional materials are added to each mixture to form layer raw materials; then the layer raw materials are respectively mixed with a silica gel matrix in a high shear mixer; the raw materials mixed with the silica gel matrix are again poured into a honeycomb structure layered mold in sequence to form a first layer, a second layer and a third layer of a high thermal conductivity boron nitride-based interface material; finally, the pre-cured material is cured at 200° C. for 4 hours to form a honeycomb structure boron nitride-based interface material. In the present application, the layer materials mixed with the silicone matrix are poured into the honeycomb structure layered mold in sequence to form the first layer, the second layer, and the third layer of the high thermal conductivity boron nitride-based interface material. The three-layer interface material structure formed by the self-healing microcapsules, magnetic nanoparticles Fe3O4, and metal aluminum foam containing thermal conductive particles between each layer of the material not only improves the thermal conductivity, mechanical strength and flexibility of the interface material, but also greatly improves the service life.
[0104] 2. The present invention uses a combination of boron nitride, graphene, nanosilver particles and nano-enhancers (carbon nanotubes or borate fibers) in this technical solution. This combination of multiple components innovatively solves the limitations of a single material in thermal conductivity or mechanical properties. This multi-component nanocomposite material provides excellent thermal conductivity and enhanced mechanical stability. Graphene and nanosilver particles greatly increase the thermal conductivity of the composite material, while carbon nanotubes and borate fibers enhance the mechanical strength and flexibility of the material, making the material suitable for high-performance industrial applications, such as effectively dissipating heat in electronic equipment and keeping the equipment working stably for a long time.
[0105] 3. The present invention adds self-healing microcapsules containing heat transfer oil to the first layer of material. These microcapsules can automatically release heat transfer oil to fill the cracks and restore the heat conduction path when the material has tiny cracks or damage. The self-healing technology significantly improves the reliability and durability of the material. Even if tiny damage occurs under high load or high temperature conditions, the material can self-repair and maintain its structural and functional integrity, thereby extending its service life and reducing maintenance costs. Magnetic nanoparticles Fe3O4 are added to the second layer of material to allow the material properties to be adjusted through an external magnetic field, changing the heat conduction path or increasing thermal isolation. The magnetic control layer provides a method for dynamically adjusting the material properties, increasing the applicability and functionality of the material. In applications that require rapid changes in thermal management strategies, such as in changing external environments, the performance and response speed of the device can be optimized by simply adjusting the magnetic field. An interface layer containing thermally conductive particles is added between each layer to enhance the thermal and mechanical connection between the layers and improve the structural integrity and thermal efficiency of the overall material. The addition of thermally conductive particles not only enhances the thermal conductivity between the layers, but also enhances the mechanical bonding between the layers, making the overall structure more stable. This design improves the performance of the material in complex application environments, especially those that require high mechanical strength and excellent thermal management.
[0106] The above is a detailed introduction to a high thermal conductivity boron nitride-based interface material and its preparation method. This article uses specific examples to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the core idea of the present invention; at the same time, for general technical personnel in this field, according to the ideas and methods of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A method for preparing a high thermal conductivity boron nitride-based interface material, characterized in that: Includes steps: S1: The boron nitride powder is surface functionalized and coated with a layer of silver; S2: mixing the treated boron nitride powder with graphene, nanosilver particles and nanoreinforcement agent to form a mixture 1, using a high shear mixer to ensure uniform dispersion of the components; the nanoreinforcement agent is selected from carbon nanotubes or borate fibers; S3: Divide the mixture 1 into three parts in the ratio of 35%:30%:35%, namely the first mixture, the second mixture and the third mixture, and add functional materials to each mixture to form the raw materials of the layer: The first mixture is added with self-healing microcapsules containing heat-conducting oil to form a first layer of raw materials, wherein the shell of the self-healing microcapsules is made of high-temperature resistant material silicone resin; The second mixture contains magnetic nanoparticles forming a second layer of raw materials; The third mixture is added with nano-aluminum metal foam to form the third layer of raw materials; S4: mixing the first layer raw material, the second layer raw material, and the third layer raw material with the silica gel matrix in a high shear mixer; S5: pouring the first layer raw material, the second layer raw material, and the third layer raw material mixed with the silica gel matrix into the honeycomb structure layered mold in order to form the first layer, the second layer, and the third layer of the high thermal conductivity boron nitride-based interface material, and pre-curing at a temperature of 150° C. for 1 hour; wherein, before pouring into the honeycomb structure layered mold, adding a silane coupling agent γ-methacryloxypropyl trimethoxysilane to each layer of the material; S6: Curing the pre-cured material at 200°C for 4 hours to form a boron nitride-based interface material with a honeycomb structure.
2. A method for preparing a high thermal conductivity boron nitride-based interface material according to claim 1, characterized in that: The surface functionalization treatment in S1 adopts a chemical vapor deposition method, and the thickness of the coated silver layer is 0.5 to 10 microns.
3. A method for preparing a high thermal conductivity boron nitride-based interface material according to claim 1, characterized in that: The average particle size of the nano silver particles ranges from 10 to 100 nanometers; in the self-healing microcapsules, the filling rate of the heat transfer oil is 50%-70% of the total volume of the microcapsules, and the average diameter of the microcapsules is 10 micrometers to 200 micrometers.
4. A method for preparing a high thermal conductivity boron nitride-based interface material according to claim 1, characterized in that: The S5 contains thermal conductive particles between each layer of material; the silicone matrix is a two-component RTV silicone, and the mixing process is carried out in a high shear mixer, the speed of the mixer is set at 1000 to 3000 rpm, and the mixing time is 5 to 15 minutes.
5. A method for preparing a high thermal conductivity boron nitride-based interface material according to claim 4, characterized in that: The preparation of the second layer involves the addition of magnetic nanoparticles Before mixing with boron nitride powder, graphene and silica matrix, nanoparticles are first obtained by high-energy ball milling. Surface modification and pre-dispersion of nanoparticles followed by application of external magnetic fields to guide the nanoparticles during the manufacturing process before curing Arrange along a predetermined path.
6. A high thermal conductivity boron nitride-based interface material, characterized in that: The first layer of the high thermal conductivity boron nitride-based interface material is composed of the following components in weight percentage: Boron nitride powder: 40%-50%, wherein the surface of the boron nitride powder is functionalized and coated with a layer of silver by chemical vapor deposition; Graphene: 10%-20%; Silica gel matrix: 10%-20%; Nano silver particles: 5%-15%; Nano-enhancer carbon nanotubes: 2%-10%, forming a three-dimensional network structure together with nano-silver particles and graphene; Self-healing microcapsules containing heat-conducting oil: 5%-15%; the shell of the self-healing microcapsules is made of high-temperature resistant silicone resin; The second layer of the high thermal conductivity boron nitride-based interface material is composed of the following components in weight percentage: Boron nitride powder: 40%-50%, wherein the surface of the boron nitride powder is functionalized and coated with a layer of silver by chemical vapor deposition; Graphene: 10%-20%; Silica gel matrix: 10%-20%; Nano silver particles: 5%-15%; Nano-enhancer carbon nanotubes: 2%-10%, forming a three-dimensional network structure together with nano-silver particles and graphene; Magnetic Nanoparticles :5%-10%; The third layer of the high thermal conductivity boron nitride-based interface material is composed of the following components in weight percentage: Boron nitride powder: 40%-50%, wherein the surface of the boron nitride powder is functionalized and coated with a layer of silver by chemical vapor deposition; Graphene: 10%-20%; Silica gel matrix: 10%-20%; Nano silver particles: 5%-15%; Nano-enhancer carbon nanotubes: 2%-10%, forming a three-dimensional network structure together with nano-silver particles and graphene; Nano aluminum metal foam: 5%-10%; Among them, the second layer is between the first layer and the third layer, and the high thermal conductivity boron nitride-based interface material has a honeycomb structure. The honeycomb structure is composed of a periodic porous network, and the diameter of each hole is between 10 microns and 100 microns.
7. A high thermal conductivity boron nitride-based interface material as claimed in claim 6, characterized in that: The thickness of the applied silver layer is 0.5 to 10 microns.
8. A high thermal conductivity boron nitride-based interface material as claimed in claim 7, characterized in that: The average particle size of the nano silver particles ranges from 10 to 100 nanometers; the shell of the self-healing microcapsule is made of silicone resin, the filling rate of the heat transfer oil is 50%-70% of the total volume of the microcapsule, and the average diameter of the microcapsule is 10 micrometers to 200 micrometers.
9. A high thermal conductivity boron nitride-based interface material as claimed in claim 8, characterized in that: Thermally conductive particles are contained between each layer of material.
10. A high thermal conductivity boron nitride-based interface material as claimed in claim 7, characterized in that: The silica gel matrix is a two-component RTV silica gel.
Citation Information
Patent Citations
Graphene / boron nitride loaded nanosilver heat-conducting special macromolecular material and preparation method thereof
CN106987123A
High-thermal-conductivity boron nitride / epoxy resin composite material and preparation method and application thereof
CN110922719A